Review of the New Caledonian species of Paroxyethira Mosely, 1924 (Trichoptera: Hydroptilidae) - Wells, A.; Johanson, K. A. (Zootaxa, 2012)
New Caledonian representation of the New Zealand-New Caledonian hydroptilid caddisfly genus Paroxyethira Mosely, 1924, is reviewed on the basis of a considerable collection from widespread New Caledonian localities. Description of 8 new species brings to 10 the known fauna for the island. Males of all New Caledonian species are illustrated, a key to adult males is provided, and the associated females are described for 6 species.